Political Polarization: Consequences for Democratic Institutions - Elinda Novita Dewi; Anggun Wida Prawira; Edyanto Edyanto (International Journal of Law and Political Authority, 2026)
Political polarization has increasingly reshaped the governance of social media, raising critical concerns regarding its impact on freedom of expression within democratic systems. This study examines how regulatory expansion, platform governance, and legal oversight interact with polarized political environments to influence expressive rights in digital spaces. Drawing on a qualitative analytical approach and extensive synthesis of contemporary democratic theory, polarization scholarship, and empirical research, the study reveals that social media regulation often operates through indirect and asymmetrical constraints rather than overt censorship. Algorithmic moderation, institutional politicization, and declining public trust emerge as key mechanisms that narrow the space for legitimate political expression. The analysis further demonstrates that the effects of regulation are contingent upon democratic resilience, particularly the strength of legal oversight, institutional independence, and civic norms. In polarized contexts where these safeguards weaken, freedom of expression becomes increasingly vulnerable to selective enforcement and expressive inequality. The study contributes to debates on digital governance by highlighting the necessity of aligning social media regulation with democratic legitimacy, pluralism, and constitutional accountability in order to sustain expressive freedom in the digital age.